Application of Digital Technologies in Law - Grudtsina, Ludmila; Guliyeva, Mehriban Elbrus kyzy; Zhdanov, Sergei; Sangadzhiev, Badma; Shestak, Victor (Jurnal Cita Hukum, 2022)
The study's purpose is to examine the nature, concepts, and grounds for the use of various types of digital technologies in law, to concisely and clearly outline the systematized foundations of scientific knowledge on the application of digital technologies in regulation and legislation on the example of the Russian Federation, with the involvement of legislative practices of foreign countries. The deductive method was the primary method of the study, which allowed us to consider the nature and foundations, forms, and methods of using digital technologies in law and legislation. In addition, the inductive method, the practice of systemic scientific analysis, and comparative legal and historical methods were used. The top way underlying the solution to the issue is to study the legal foundations and features of using digital technologies in law. The study proves the unsolved theoretical problem of scientific understanding of the types and forms of application of digital technologies in law in the example of the Russian Federation and some countries of the world. The authors argue that digital technologies store much information, thereby simplifying the transaction system. It allows us to receive information quickly and, as a result, significantly save time and speed up the process of transferring data.